â€œSay No Bad Touchâ€: The Use of Puppet Show to Promote Childrenâ€™s Awareness of Their Private Parts - Puspitasari, Dewi; Maulida, Chusna; Noviyanto, Norma (IAIN Pekalongan, 2019)
In this study, we set puppet as the media to educate them concerning how to prevent sexual harassment as the lack of information of private area among children. The preventive program was built from the infusing important aspects from very beginning age. Series of actions were implemented: specified characters from Big Book story (a boy, a girl, a mother, a father, an aunt, an uncle, a stranger, a police, and a teacher) as puppet characters, colored the puppets, to played them due to the plot of the story. The research proved that visual aid helped the process of instilling the core message to children, and empowering them to say no against bad touch. In the process of transferring the message, certain aspects must be taken for granted. As private parts are not included in easy to be digested theme for children, considering the lack of information given by parents, the material transferred & language used to these young learners must be well tailored to childrenâ€™s age.